Distribution, stability, and protein interactions of Aflatoxin M1 in fresh cheese - Chavarría Molina, Guadalupe (2017)
Aflatoxin M1 (AFM1), a metabolite resulting from the hepatic metabolism of aflatoxin B1, is a potential carcinogen that can be found in milk, cheese, and others dairy products. In this work, we aimed to elucidate the distribution and fate of AFM1 in fresh cheese and whey during cheese manufacturing and storage as well as the level of interaction of this toxin with various milk, cheese, and whey proteins. Additionally, we analyzed the in vitro behavior of casein, α-lactalbumin, β-lactoglobulin, bovine serum albumin (BSA), lactoferrin, and mixtures thereof, with a fixed concentration of AFM1 after covalent crosslinking. Our results show that up to 70% of the AFM1 levels present in milk spiked with 0.5 and 1.5 μg L−1 are released in whey during fresh cheese manufacturing. The whey and milk proteins with more AFM1 molecules bound were α-lactalbumin and casein, with 88% and 81%, respectively. We also observed a substantial decrement in AFM1 concentration during ripening that correlated inversely with plate counts of lactic acid bacteria and directly with the whey-draining process that occurs during fresh cheese maturation or storage. This knowledge may serve as a basis for interventions in the dairy industry aiming to increase the security of cheese and other dairy products.